Epistemologi Pendidikan Islam dalam Kurikulum Merdeka Belajar - Firza Alkhoiri; Zikri Dwi Marpendra; Herlini Puspika Sari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study explores the epistemological foundation of Islamic education in the context of the Merdeka Curriculum implementation in Indonesia. The research aims to analyze how Islamic epistemology—which integrates revelation, reason, and experience—can be harmonized with the principles of independent learning that emphasize flexibility, contextual understanding, and character development. Using a qualitative descriptive approach, this study collects data through literature review and content analysis of relevant academic works and policy documents. The findings show that the integration of Islamic epistemology provides a philosophical framework that strengthens the spiritual and moral dimensions of education while maintaining academic autonomy. The implications highlight the importance of teachers’ capacity, curriculum adaptation, and policy support to ensure that the Merdeka Curriculum remains grounded in Islamic educational values. This study contributes to the discourse on contemporary Islamic education by proposing an integrative model that aligns faith-based knowledge with modern educational paradigms.